1732. Single Center Dalbavancin Experience: A cost saving surprise in people with substance use disorder. (15th December 2022) - Nakagami, Peter; Morita, Kazumi; Schultz, Sara K; Rodriguez, Leah
Abstract: Background: Dalbavancin is a lipoglycopeptide antibiotic that has efficacy in the treatment of skin/soft tissue infections secondary to Gram-positive organisms. Given its long half-life, there has been increasing use for other indications including osteomyelitis, joint infections, and bacteremia. Our goal was to evaluate the indications for usage in our health system, characteristics of the patients receiving dalbavancin, and outcomes with recurrence of infection and cost to the health system. Methods: A retrospective chart review was conducted reviewing all patients who were ordered dalbavancin in the Temple health system between Nov 1, 2019 to Mar 31, 2021. Charts were reviewed in Epic with data collection in REDCap. Results: 34 orders for dalbavancin use were reviewed, representing 33 unique patients with 31 instances of dalbavancin administered. The majority of patients were male (79%) and had substance use disorder (88%). 97% of patients had formal ID consult. The majority of the patients were recommended dalbavancin due to concerns for adherence to prolonged oral regimens (17) or difficulties with SNF placement (19). The most common indications were bone and joint infections (16, 5 of which involved prosthesis) and bacteremia (9). 94% of patient received effective antibiotics prior to dalbavancin, with a median of 4 days. 75% of patients received their full prescribed course of dalbavancin. Only 1 adverse event was reported (itching and skin sloughing). At the time of writing, 12/23 (52%) of patients who were more than 90 days from a completed dalbavacin course returned for treatment for an infection at the same site within 90 days. Cost savings estimated from the alternate planned antibiotics and facility stay were calculated out to $1.47 million and 445 total hospital days were averted. Conclusion: Our results show that dalbavancin use at our institution had minimal adverse reactions and were used to treat infections beyond skin/soft tissue infections in a population of predominantly people with substance use disorder. Our early experience with this drug uncovered potentially significant cost savings with dalbavancin due to avoided hospital days. Disclosures: All Authors : No reported disclosures.